KAIZEN DAN IMPLEMENTASINYA TERHADAP FAKTOR-FAKTOR YANG MENINGKATKAN KINERJA KARYAWAN PERUSAHAAN - Boma Jonaldy; Nur Anisah (Pusat Riset dan Inovasi Nasional, 2022)
Kaizen is one of the company's strategies in increasing business productivity. In addition to being related to production management, kaizen is also related to human resource management. This can be in line with increase in employee performance. The implementation of kaizen on the factors of improving employee performance can not necessarily be done instantly, there needs to be a thorough adaptation that takes a long time to implement. In case, the researchers try to examine